Profil PAsien Sindromik Kraniosinostosis selama 5 Tahun di dr.Soetomo Hospital Surabaya - Adinda Widita; Magda Hutagalung; Indri Lakhsmi Putri (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2017)
Craniosynostosis is a premature cover of one or more sutures, which may occur as part of syndrome (syndromic) or as a separate defect / isolated defect (nonsyndromic). Cohen and Kreirborg state the incidence of Apert and Crouzon syndromes of 15.5: 1,000,000 and 16.5: 1,000,000 per birth. The incidence of craniosynostosis in Indonesia still not handled properly, as well as low recognition in this disorder. RSUD Dr. Soetomo as an eastern referral hospital, which has one of the centers of plastic surgery education in Indonesia, where craniosynostosis syndromic often occurs, so we have total cases handled in Indonesia. This is a retrospective descriptive study discusses more about the profile of patients syndromic craniosynostosis for 5 years in dr. Soetomo Surabaya, performed on twenty-four first syndromic craniosynostosis patients at Dr. Soetomo Surabaya period 1 January 2008 - 31 December 2013. Out of 24 total patients, 12 cases of apert (29%), 6 crouton cases (54%) and 3 cases of Pfeiffer (17%) were obtained. Based on sex, more commonly found in women (54%). With the most common age, the patient comes first is aged 5-10 years (37%). Each patient has an average of 2 surgeries, with a type of surgical action on cranial vault remodeling patients. Abnormalities of syndromic craniosinostosis found the most common in women and apert syndrome in RSUD dr.Sutomo. Where the most common age when the arrival of 5-10 years, caused by the late diagnosis of the disorder.